1988
DOI: 10.1002/macp.1988.021891107
|View full text |Cite
|
Sign up to set email alerts
|

Critical opalescence of polymer solutions at high pressures

Abstract: With a new type of high-pressure cell the angular dependence of light scattering intensities at scattering angles B between 30" and 150" can be measured as a function of pressure P . The linear extrapolation of (v)-I as a function of sin2 (8/2) to B = 0 does not show an angular dependence of the scattering intensities. For this result the term including sin' (8/2) in Debye's equation for the critical opalescence vanishes. The reason for_this is probably due to the low molar mass of the polystyrene (number-aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…More recently Smith, Freeman and Hall reported measurements on low MW polypropylene oxide near the glass transition at 253 K (250 < P /MPa < 390). To our knowledge the present data represent the first DLS measurements on polymer solutions in the vicinity of pressure induced demixing, although Kiepen and Borchard, Steinhoff, Rullmann, Kuhne, and Alig, and Xiong and Kiran have described cells used for static light scattering of polymer solutions during pressure induced precipitation (0 < P /MPa < ∼80), and Lechner and Mattern reported static and dynamic light scattering measurements on poly(vinyl alcohol)/water/alcohol solutions at high pressure and temperature, but not in the vicinity of the phase transition.…”
Section: Introductionmentioning
confidence: 83%
“…More recently Smith, Freeman and Hall reported measurements on low MW polypropylene oxide near the glass transition at 253 K (250 < P /MPa < 390). To our knowledge the present data represent the first DLS measurements on polymer solutions in the vicinity of pressure induced demixing, although Kiepen and Borchard, Steinhoff, Rullmann, Kuhne, and Alig, and Xiong and Kiran have described cells used for static light scattering of polymer solutions during pressure induced precipitation (0 < P /MPa < ∼80), and Lechner and Mattern reported static and dynamic light scattering measurements on poly(vinyl alcohol)/water/alcohol solutions at high pressure and temperature, but not in the vicinity of the phase transition.…”
Section: Introductionmentioning
confidence: 83%
“…Some protein or polymer solutions often cause opalescence or turbidity under their critical conditions. This is the critical opalescence caused by light scattering from microregions of slightly different density or the larger structuralized aggregates. Takushi et al found that a boiled egg turns from whitish to opaque (close to transparency) at subzero temperatures.…”
Section: Introductionmentioning
confidence: 99%